(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the development of water legislation of the Republic of Kazakhstan. The Republic of Kazakhstan begins to experience water shortages and may face a significant shortage of water resources. The problem of water security in conditions of limited water resources and the vulnerability is seen as a threat to national security. Today, countries in the region seeking to counter the threat of water scarcity in many ways - from the forced water savings achieved through the establishment of state control, to large-scale capital investment in the water sector to overcome the water shortage. The publication also relatively problem rassmativaetsya water legislation, methods and ways of implementing the programs of Arab extraction and consumption of water resources, and legal problems. Key words: Waterresources, water safety, water code, water law, protection of water bodies.